EXPLORING PREFERENCES FOR COUNTERFEIT AND GENERIC GOODS AMONG EGYPTIAN SHOPPERS: A STUDY OF CONTRIBUTORY ELEMENTS - Awad, Ahmed M.; Al-Masri , Heba Y. (Ayden International Journal of Banking, Finance and Technology, 2024)
The counterfeit market is a growing concern globally, and this study aims to investigate the factors influencing consumers' preferences for counterfeit and generic products in Egypt. Through surveying 271 consumers, this research concludes that demographic variables, perceived risk, and prior experience are insignificant factors in choosing counterfeits or generics, while price, taste and preferences, quality, the price of related products, subjective norms, and expected prices significantly affect consumer preferences and demand. Consumers who prioritize quality, expected prices, and the price of related products are more likely to purchase generics, while those whose tastes and preferences are influenced by others' expectations, prestige, and acceptance are more likely to purchase counterfeits. Moreover, price negatively affects consumer demand, while the price of related products and expected prices affect consumer preferences positively toward generics and negatively toward counterfeits. These findings provide insights for profit-maximizing noncounterfeit producers to understand consumer behavior and allocate resources efficiently. The government can also use this information to apply more efficient policies regarding the counterfeit market.This study contributes to the existing literature by examining the demand side of the counterfeit market, which is crucial for understanding the market's impact on the economy. It also fills the literature gap by analyzing the factors influencing consumers' preferences for counterfeit and generic products in Egypt. This study's limitations are also discussed, and recommendations for future research are provided.